Post-COVID-19 syndrome: morpho-functional abnormalities of the heart and arrhythmias - M. V. Chistyakova; D. N. Zaitsev; A. V. Govorin; N. A. Medvedeva; A. A. Kurokhtina (Российский кардиологический журнал, 2021)
Aim. To study the myocardial morpho-functional abnormalities, the incidence and nature of cardiac arrhythmias in patients 3 months after the coronavirus disease 2019 (COVID-19).Material and methods. The study included 77 patients (mean age, 35,9 years) treated for coronavirus infection, which underwent echocardiography and 24-hour Holter monitoring 3 months after COVID-19. The patients were divided into 3 groups: group 1 — 31 patients with upper respiratory tract involvement; group 2 — 27 patients with bilateral pneumonia (CT grade 1, 2), 3 — 19 patients with severe pneumonia (CT grade 3, 4). Statistical processing was carried out using Statistica 10.0.Results. According to echocardiography, the peak tricuspid late diastolic velocity and isovolumetric contraction time in all groups increased (P<0,001). The tricuspid and mitral Em/Am ratio decreased depending on the disease severity. In group 3, the right ventricular and atrial size increased (P<0,001). The pulmonary artery systolic pressure, left atrial volume in patients of the 2nd and 3rd groups was higher than in the control one (P<0,001). In group 1 and 2 patients, the regional strain in basal and basal/middle segments decreased, respectively, while, in group 3, not only regional but also global left ventricular (LV) strain decreased (P<0,001). In all groups, cardiac arrhythmias and pericardial effusion were found. The relationship was established between coronavirus activity and the structural and functional myocardial parameters (P<0,001).Conclusion. Cardiovascular injury 3 months after COVID-19 was found in 71%, 93%, and 95% of patients with mild, moderate and severe course. In mild course patients, a decrease in regional myocardial strain in LV basal segments, signs of past pericarditis, and various cardiac arrhythmias were noted. In patients of moderate severity, these changes were more pronounced and were accompanied by an additional decrease in regional strain in LV middle segments, impaired right ventricular diastole and increased pulmonary artery pressure. In severe patients, in addition to the above changes, dilatation of the right heart and inferior vena cava was recorded, as well as LV diastolic and global systolic function decreased.